'Seeing is believing': arguing for diagnostic laparoscopy as a diagnostic test for endometriosis. Issue 3 (4th July 2022) - Mak, Jason; Leonardi, Mathew; Condous, George
Abstract : Lay summary: Endometriosis is a benign disease that can cause pain and infertility in women. Debate exists over how endometriosis should best be diagnosed. On one hand, endometriosis can be diagnosed by directly examining pelvic anatomy via a surgical procedure known as diagnostic laparoscopy. On the other hand, the disease can be diagnosed via non-surgical means such as using medical imaging, the symptoms described by the patient and whether the patient responds to non-surgical therapies such as medication. In this debate article, we argue in favour of diagnostic laparoscopy. We review the safety of the procedure, compare the ability of diagnostic laparoscopy vs medical imaging to detect endometriosis and consider the benefits of formally diagnosing or ruling out the condition.